Transmedial presence of verbal texts in architecture and public space. Between informativity and emotivity - Chrzanowska-Kluczewska, Elżbieta (Cognition, Communication, Discourse, 2024)
From the semiotic viewpoint, architectonic structures and the surrounding public spaces can be seen as texts to be read and interpreted within proper historical, social, and cultural contexts. In addition, they are almost always multimodal, that is polysemiotic texts whose content becomes complemented with pictorial elements (paintings, sculptures), with written or oral language and, on occasion, with music. I intend to focus specifically on the presence of verbal texts inside, on or around buildings (mostly within an urban space), which is a case of textual embedment. Functions of written inserts, inscriptions, signboards, tablets, posters, banners, graffiti, etc. are multifarious. They range from informational and explanatory, to devotional, to political–critical, to – in the end – poetic, experimental, creative, funny, and ironical. Aesthetically, they often enrich but sometimes violate architecture and public space. The following types of verbal texts will be considered briefly, according to their content: 1) up-to-date information (warnings, advertisements, etc.); 2) historical-institutional information; 3) religious-devotional (including critical) information; 4) political commentaries; 5) poetic and experimental creations, mostly artistic critical games played by conceptual and post-modern artists. Several of my examples qualify as instances of urban creativity, specifically street art and graffiti of resistance (cf. Awad & Wagoner, 2017; Stampoulidis, 2019). In the spirit of cognitive semiotics, defined by Zlatev, Sonesson, and Konderak (2016) as the transdisciplinary, conceptual-empirical study of meaning, mind and communication, this article (based on a corpus of twenty-six inscriptions gathered from many international locations) raises the issue of the interplay of informativity and emotional load contained in verbal texts immersed in public settings. Undoubtedly, the message conveyed by architectural carriers and urban space contributes synergically to the overall meaning of the verbal messages that accompany them.